In Silico Medicinal and Pharmacological Evaluation of Phytochemical Constituents from the Root Bark Extract of Enantia Chlorantha as Potential Antimalarial Drugs - Ibrahim, Sulyman; Lukman, Halimat; Ayipo, Yusuf; Babamale, Halimah; Abdulkadir, Fatimah; Hamid, Abdulmumeen; Zubair, Marili; Atolani, Olubunmi (Journal of Pure & Applied Sciences, 2024)
Enantia chlorantha is a preferred medicinal plant among local healthcare providers in Nigeria for the treatment of malaria. While numerous studies have validated its potency, this updated report investigates the mechanistic and synergistic phytochemicals of the plant responsible for its antimalarial properties. The chemical composition of the methanol root bark extract was analyzed using Gas Chromatography-Mass Spectroscopy (GC-MS). The in silico pharmacological and toxicological profiles were determined using SwissADME and Protox II online servers. The simulation modeled the interaction between phytochemicals and Plasmodium falciparum dihydrofolate reductase-thymidylate synthase enzymes implicated in the pathogenic process of malaria via molecular docking. Docking was performed using PyRx-0.8 software coupled with AutoDock Vina. The findings indicate that N-[2-(2-Hydroxy-1-naphthylmethyleneamino)-4-methoxyphenyl] (-9.4 kcal/mol), squalene (-8.6 kcal/mol), curlone (-7.7 kcal/mol), tumerone (-7.8 kcal/mol), and ar-tumerone (-7.9 kcal/mol) demonstrated stronger binding affinities to the target protein compared to standard antimalarial medications such as artemether (-7.6 kcal/mol) and lumefantrine (-6.6 kcal/mol). These results were further confirmed by the phytochemicals' binding free energy ΛGBind (MMGBSA) values: N-[2-(2-Hydroxy-1-naphthylmethyleneamino)-4-methoxyphenyl] acetamide (-64.14 kcal/mol), squalene (-63.74 kcal/mol), and tumerone (-41.78 kcal/mol), compared to artemether (-23.39 kcal/mol) and lumefantrine (-43.01 kcal/mol). The toxicological profile suggests that the phytochemicals from E. chlorantha demonstrated reasonably low toxicity, comparable to standard drugs.